The Effects of Peroxiredoxin 6 Gene rs41055489 Variation on Oxidative Stress Mechanisms in Human Model Organism - (:unkn) unknown (BEZMIALEM VAKIF UNIV, 2015)
Objective: Peroxiredoxins (Prx) belong to peroxidase type enzyme group which reduce redox active cysteine residues. The aim of this study was to determine the allele frequencies of Prx 6 gene rs41055489 polymorphism in zebrafish and in which extent may improve protective measures against oxidative stress indicators. Methods: The Prx6 gene rs41055489 genotypes were determined with qPCR method in zebrafish exposed to different doses of heavy metals. Additionally, the glutathion (GSH), malondialdehide (MDA) and catalase (CAT) levels were measured. Results: The Prx6 gene rs41055489 genotype frequencies were determined respectively as 97.7% for homozygous wild type (A/A), 2.3% for heterozygous (A/C) in group. The polymorphic genotype (C/C) was not detected in our study group. Conclusion: Prx6 rs41055489 heterozygous gene polymorphism have been observed to inhibit defence mechanisms.
Keywords: Zebra fish; Peroxiredoxins 6 gene; rs41055489 polymorphism; heavy metal; oxidative stress; TILAPIA OREOCHROMIS-NILOTICUS; RAINBOW-TROUT; ANTIOXIDANT; CADMIUM; RESPONSES; EXPOSURE; CELLS; TISSUES; SYSTEMS; CLONING